2020
DOI: 10.1108/ijchm-04-2020-0259
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of AI-based chatbots for hospitality and tourism

Abstract: Purpose This study aims to investigate the customers’ behavioral intention and actual usage (AUE) of artificial intelligence (AI)-powered chatbots for hospitality and tourism in India by extending the technology adoption model (TAM) with context-specific variables. Design/methodology/approach To understand the customers’ behavioral intention and AUE of AI-powered chatbots for tourism, the mixed-method design was used whereby qualitative and quantitative techniques were combined. A total of 36 senior managers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
340
2
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(367 citation statements)
references
References 114 publications
(149 reference statements)
13
340
2
12
Order By: Relevance
“…The second finding of the study revealed that hotel customers' perceptions of disadvantage regarding service robots negatively affected their intention to use robots. Customers who have technology anxiety may be especially worried and afraid about using new technology [10]. There may be customers who prefer to chat with humans rather than robots.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second finding of the study revealed that hotel customers' perceptions of disadvantage regarding service robots negatively affected their intention to use robots. Customers who have technology anxiety may be especially worried and afraid about using new technology [10]. There may be customers who prefer to chat with humans rather than robots.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, technology anxiety expresses the concerns and fears of consumers about using new technology. In this context, technology anxiety is recognized as an essential psychological precursor affecting the adoption of new technology [10]. In other words, a customer's willingness to adopt new technology hinges on their confidence in how valuable that technology will be [29].…”
Section: Service Robots In Hospitalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Their study is focused on young consumers and indicates that frequent users of robotic experiences do not pay much attention to robotic embodiment: the more knowledge consumers have about how automation and nonhuman agents work, the less important robot morphology is. Pillai and Sivathanu's [78] study of customers' behavioral intentions towards robotization noted this technological aspect among several aspects that require careful attention in designing successful HRIs: the perceived intelligence of the service robot, trust relations, technology anxiety, and the need to reduce customer uncertainties (see also [79,80]).…”
Section: Anthropomorphism Zoomorphism and Robotic Embodimentmentioning
confidence: 99%
“…McCartney and McCartney (2020) investigated the legislative, technological and risk factors for hospitality companies adopting service robots to their workplace. Though the manager’s intention to adopt chatbot is not influenced by the technological anxiety (TXN), TXN is an important factor for tourists (Pillai and Sivathanu, 2020). Christou et al (2020) focused on the morphology of service robots and their study defined that tourists prefer anthropomorphic robots possessing humanlike cues among various features of service robots.…”
Section: Literature Reviewmentioning
confidence: 99%